Bariatric surgery for young people with obesity and results of laparoscopic bariatric surgery in Serbia - Radoica Jokic (Elsevier, 2024)
Bariatrics is the branch of medicine that deals with the causes, prevention and treatment of obesity. Bariatric surgery is a surgical weight loss procedure used to treat extreme obesity. Minimal invasive surgery became standard procedure for the treatment of obesity as well. Gastric banding (GB) usually takes 45-60 min, but in USA it is not approved for use in teenagers. Laparoscopic Roux-en Y Gastric Bypass (LRYGB) is operation where proximal pouch of stomach is anastomosied with short intestinal Roux limb. Laparoscopic gastric sleeve (LGS) procedure is laparoscopic operation during which surgeon removes about ¾ of the patients stomach along the greater curvature and create a new stomach in the shape of tube. When compared to other weight-loss surgeries, sleeve gastrectomy is technically easier with relatively less morbidity. Gastric sleeve procedure has been performed in our hospital on three patients aged 15 to 17 years. One male and two female patients, all with BMI more than 39 kg/m2. Postoperative follow up was without any complications. This small study demonstrated that children aged ≤ 18 years could successfully undergo LGS with a significant reduction in weight and BMI. Although there were no short- or long-term complications in our study, the small sample size necessitates larger studies. Results of future research will create future clinical decisions to solve the epidemic of obesity.